Official documents on digital education in Higher Education in Brazil and Portugal: A content analysis - Bressan, Douglas (2025)
Introduction: This study explores the intersection between education and ICT in Higher Education, focusing on the digital transition (DT) and the development of digital competences (DC) as essential factors to modernize education and promote social and digital inclusion, through a comparison between Brazil and Portugal. Background: This qualitative research analyzes Brazilian and Portuguese official documents through exploratory research, which were collected, categorized, and organized using the NVivo 14 platform. Bardin’s Content Analysis was employed to interpret the data, providing insights into how these documents address DT and DC in both countries. Discussion: The analysis of the documents revealed differences and similarities between Brazil and Portugal regarding DT and DC in higher education. Portugal stands out for its more robust policies, while Brazil faces challenges related to teachers’ continuing education and inequality.